2021
DOI: 10.1186/s12890-021-01403-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of long-acting muscarinic antagonist and long-acting β2 agonist fixed-dose combinations in patients with chronic obstructive pulmonary disease

Abstract: Background In chronic obstructive pulmonary disease (COPD) patients, combination treatment with long-acting muscarinic antagonist (LAMA) and long-acting β2 agonist (LABA) increases forced expiratory volume in one second and reduces symptoms compared to monotherapy. In Japan, three different once-daily fixed-dose combinations (FDCs) have been prescribed since 2015, although a direct comparison of these FDCs has never been performed. The objective of the present study was to compare the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, a real-world study from Taiwan reported that TIO/OLO was superior to IND/GLY and UMEC/VIL in relation to FEV1 (98.7 vs. 65.2 vs. 64.4 mL, respectively; p < 0.001) and FVC (127.3 vs. 58.2 vs. 79.1 mL; p < 0.001) after 12 months of treatment [ 15 ]. A prospective direct comparison study (open-labeled) in Japan of the three once-daily LABA/LAMA FDCs reported no significant differences in spirometry parameters after 12 weeks of treatment [ 16 ]. These few studies appear to be contradictory in their findings; however, this could be explained by the different study designs, the different patient cohorts, and the differences between retrospective real-world studies and RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a real-world study from Taiwan reported that TIO/OLO was superior to IND/GLY and UMEC/VIL in relation to FEV1 (98.7 vs. 65.2 vs. 64.4 mL, respectively; p < 0.001) and FVC (127.3 vs. 58.2 vs. 79.1 mL; p < 0.001) after 12 months of treatment [ 15 ]. A prospective direct comparison study (open-labeled) in Japan of the three once-daily LABA/LAMA FDCs reported no significant differences in spirometry parameters after 12 weeks of treatment [ 16 ]. These few studies appear to be contradictory in their findings; however, this could be explained by the different study designs, the different patient cohorts, and the differences between retrospective real-world studies and RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al conducted a real-word study in Taiwan and reported that TIO/OLO resulted in superior lung function improvement (FEV1 and force vital capacity (FVC)) and reduced AEs, compared with the other regimens (IND/GLY and UMEC/VI) [ 15 ]. Muraki et al reported that there were no significant differences in the COPD Assessment Test (CAT), the modified Medical Research Council (mMRC) dyspnea questionnaire, and spirometry items following the administration of the three FDCs [ 16 ]. The efficacy of dual bronchodilators for lung function improvement are variable, and there are many factors that can affect the efficiency of medication in real-world practice, such as adherence to medication, the frequency of administration, the role of the device, and the patients’ understanding and views of the disease and treatment [ 17 , 18 , 19 ]; these factors cannot be seen or controlled for in randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%